2022
DOI: 10.1136/jnis-2022-019134
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus imaging characteristics within acute ischemic stroke: similarities and interdependence

Abstract: BackgroundThe effects of thrombus imaging characteristics on procedural and clinical outcomes after ischemic stroke are increasingly being studied. These thrombus characteristics – for eg, size, location, and density – are commonly analyzed as separate entities. However, it is known that some of these thrombus characteristics are strongly related. Multicollinearity can lead to unreliable prediction models. We aimed to determine the distribution, correlation and clustering of thrombus imaging characteristics ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Thrombus length, density, and perviousness were measured and reported previously. 3,21 Outcome Measures and Statistical Analyses Our primary outcome was functional outcome as measured with the ordinal modified Rankin Scale (mRS) 90 days after acute ischemic stroke. Ordinal mRS values were inverted and studied with a shift analysis in line with previous studies of the MR CLEAN Registry.…”
Section: Thrombus Measurementsmentioning
confidence: 99%
“…Thrombus length, density, and perviousness were measured and reported previously. 3,21 Outcome Measures and Statistical Analyses Our primary outcome was functional outcome as measured with the ordinal modified Rankin Scale (mRS) 90 days after acute ischemic stroke. Ordinal mRS values were inverted and studied with a shift analysis in line with previous studies of the MR CLEAN Registry.…”
Section: Thrombus Measurementsmentioning
confidence: 99%
“…Nevertheless, some binary target variables can be useful, such as the first pass effect in endovascular treatment, the recanalization following IV-tPA administration, the embolization, or the hemorrhage following intervention with endovascular treatment. However, thrombi population spans a large variability [89]. Prediction of thrombi biology in terms of conventional composition categorization is of limited value, when spatial heterogeneity becomes recognized as an influencing factor for thrombus response to treatment [97].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study using the MR CLEAN Registry dataset used unsupervised clustering with the purpose of grouping thrombi based on the CT image findings according to 1) occlusion location and 2) thrombus length, density and perviousness [89] (Supplementary material Table S5). The study found that thrombus imaging characteristics form a continuum spectrum, in which a given single thrombus variable is accompanied by a large variety of other characteristics, and as such, grouping thrombi in archetypes is not adequate.…”
Section: Using Ai To Classify Thrombi According To Ct Characteristicsmentioning
confidence: 99%
“…The data collection and thrombus imaging characteristics methods from the MR CLEAN Registry have already been described in detail previously [24,25]. The followed patient workup is in line with the one described here (our hospital is one of the MR CLEAN centers).…”
Section: Mr Clean Databasementioning
confidence: 99%
“…A chart of thrombus imaging measurements in the early-recanalized group can be found in Supplemental Figure S2. For the registry patients, such a chart is presented in [25]. ER-LVO patients had fewer ICA occlusions (1% vs. 23%, p < 0.01 after Bonferroni correction) and more M2 occlusions (32% vs. 13%, p < 0.01 after Bonferroni correction).…”
Section: Patient and Thrombus Imaging Characteristicsmentioning
confidence: 99%